IMPLEMENTATION OF GUIDED INQUIRY PHYSICS INSTRUCTION TO INCREASE AN UNDERSTANDING CONCEPT AND TO DEVELOP THE STUDENTS' CHARACTER CONSERVATION (Jurnal Pendidikan Fisika Indonesia, 2016)
The Measurement Concepts Instruction (MCI) is carried out by implementation of guided inquiry experiment  model. The objectives is to develop the understanding concept and SMA students' character. The method used experiment educational research, with post- test control group design. The data of the understanding on property and measurement is collected by essay test and an observation sheets for students' character conservation. The subject of tutorial and non tutorial groups consist of 32 students respectively. The data were analyzed by t test and correlation analysis. The results showed a) the positive correlation between students' character and mastery on concept in high category (p = 0.002) and b) students' character conservation is significantly difference between tutorial and non tutorial groups. It can be concluded that the implementation of the guided inquiry experiment model to effective increase the understanding property and measurement and to develop students' character of senior high school students.Pembelajaran Fisika (PF) dilaksanakan melalui implementasi model eksperimen inkuiri terbimbing. Tujuan utama penelitian ini untuk mengungkap konsep besaran dan pengukuran dan mengembangkan nilai karakter konservasi siswa SMA. Metode penelitian ialah eksperimen kependidikan dengan post-test control group design digunakan. Subjek penelitian adalah kelompok perlakuan dengan tutorial dan non tutorial masing-masing 32 siswa. Data penelitian konsep besaran dan pengukuran dan nilai karakter konservasi dikumpulkan dengan tes uraian dan lembar observasi. Data dianalisis menggunakan uji t dan uji korelasi. Hasil penelitian yaitu: a)  ditemukan korelasi positif antara nilai karakter konservasi dan penguasaan konsep besaran dan pengukuran pada kategori tinggi dan sangat signifikan (p = 0,002), dan  b) diperoleh perbedaan penguasaan konsep yang signifikan antara kelompok tutorial dan non tutorial. Simpulan penelitian bahwa implementasi model eksperimen inkuiri terbimbing efektif untuk meningkatkan penguasaan besaran dan pengukuran dan mengembangkan nilai karakter konservasi siswa SMA.